2022
DOI: 10.1021/acs.energyfuels.2c01727
|View full text |Cite
|
Sign up to set email alerts
|

3D/0D Cu3SnS4/CeO2 Heterojunction Photocatalyst with Dual Redox Pairs Synergistically Promotes the Photocatalytic Reduction of CO2

Abstract: As an inexpensive bimetallic sulfide with a narrow band gap, Cu3SnS4 has been widely used in solar-energy-driven catalytic reactions. However, the traditional tetragonal Cu3SnS4 has the inherent defect of fewer surface active sites and poor photogenerated carrier transport performance, which requires further modification to improve the CO2 photocatalytic reduction performance of tetragonal Cu3SnS4. In this work, the Cu3SnS4/CeO2 binary composites with dual redox pairs of Ce4+/Ce3+ and Cu2+/Cu+ were successfull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 51 publications
0
9
0
Order By: Relevance
“…85−87 Electrons and holes cannot be separated and transferred from photocatalyst A to catalyst B in Type III heterojunction photocatalysts because photocatalyst A's valence band (VB) and conduction band (CB) are higher than photocatalyst B's valence band and conduction band (Figure 6c). Wang et al 88 successfully designed and synthesized Cu 3 SnS 4 / CeO 2 binary composites with Ce 4+ /Ce 3+ and Cu 2+ /Cu + dual redox pairs by a simple solvothermal method (Figure 7a). It was shown that Cu 3 SnS 4 /CeO 2 's photochemical characteristics were greatly enhanced by the presence of double redox pairs and heterojunctions.…”
Section: Heterojunctionmentioning
confidence: 99%
See 2 more Smart Citations
“…85−87 Electrons and holes cannot be separated and transferred from photocatalyst A to catalyst B in Type III heterojunction photocatalysts because photocatalyst A's valence band (VB) and conduction band (CB) are higher than photocatalyst B's valence band and conduction band (Figure 6c). Wang et al 88 successfully designed and synthesized Cu 3 SnS 4 / CeO 2 binary composites with Ce 4+ /Ce 3+ and Cu 2+ /Cu + dual redox pairs by a simple solvothermal method (Figure 7a). It was shown that Cu 3 SnS 4 /CeO 2 's photochemical characteristics were greatly enhanced by the presence of double redox pairs and heterojunctions.…”
Section: Heterojunctionmentioning
confidence: 99%
“…(a) Schematic diagram of CO 2 reduction mechanism on Cu 3 SnS 4 /CeO 2 composites. Reproduced with permission from ref . Copyright 2022, American Chemical Society.…”
Section: Heterojunctionmentioning
confidence: 99%
See 1 more Smart Citation
“…One alternative gaining a lot of focus worldwide is converting CO 2 into value-added products. There are numerous ways of transforming CO 2 to valuable products, viz., thermocatalysis, biocatalysis, , radiolysis, , and photochemical (PC), electrochemical (EC) and photoelectrochemical (PEC) techniques. The PC technique involves incorporating renewable solar energy for transforming CO 2 to produce valuable products. In contrast to the PEC process, it does not require any external potential bias and can be performed under ambient pressure and temperature conditions .…”
Section: Introductionmentioning
confidence: 99%
“…22,25 At present, the main photoactive materials are metal oxides, 26 metal chalcogenides, 27 MXenes, 28 covalent organic frameworks (COFs), 29 and metal–organic frameworks (MOFs). 30 Among the above mentioned nanomaterials, Cu 3 SnS 4 is a kind of metal chalcogenides with excellent photo-stability, 31 narrow bandgap (1.2–1.6 eV), high oxidation resistance/acid resistance, and high absorption coefficient, 32,33 making it a promising photosensitive material in the fields of photovoltaics, 34,35 photocatalysis, 36,37 thermoelectric, 38 electrocatalytic, 39 and pollutant degradation. 40 Thus, we believe that Cu 3 SnS 4 has the potential of fabricating PEC immunosensors with the advantages of fast response, high sensitivity, and specificity.…”
Section: Introductionmentioning
confidence: 99%